أثر الدروس العملية على سمة الشجاعة لدى طلبة كلية التربية الرياضية ((دراسة مسحية على طلاب السنة الأولى وطالباتها في كلية التربية الرياضية في جامعة تشرين للعام الدراسي 2007-2008 )) (Latakia University Journal -Medical Sciences Series, 2019)
تعد سمة الشجاعة إحدى السمات الانفعالية الأساسية التي يتطلبها الأداء الرياضي الناجح والمميز. لذا يسعى المختصون إلى تنمية هذه السمة من خلال البرامج المتعددة للحصول على أداء مميز . وبرنامج الدروس العملية في كلية التربية الرياضية من بين هذه البرامج التي تهدف إلى تنمية الشجاعة من ضمن تنمية السمات الانفعالية كأحد أهدافها. والبحث يهدف إلى التعرف على مدى تأثير هذه الدروس على تنمية سمة الشجاعة، إذ قيست هذه السمة لدى الطلاب والطالبات في كلية التربية الرياضية في جامعة تشرين للعام 2007 – 2008 باستخدام اختبار الشجاعة على عينة مكونة من (18) طالبة و(42) طالباً من طلبة السنة الأولى. وأهم النتائج التي توصل إليها البحث إن برنامج الدروس العلمية كان أكثر تأثيرا على الطالبات من الطلاب،  ومستوى الشجاعة لدى الطلاب كان أعلى منه لدى الطالبات في بداية العام الدراسي . وكان متقاربا في نهاية العام. Bravery is considered one of the basic emotional attributes, which a successful and distinctive sport performance requires. Therefore, specialists are doing their best to acquire this quality through various programs. The program of practical lectures at the Faculty of Sport Education is one of these programs, which aims to develop courage within the development of emotional attributes. This research tries to how those lectures affect the progress of brave attributes by administering a courage test to first year students in the Faculty of Sport Education Faculty Education, Tishreen University in   2007 – 2008. The sample was composed of 42 male and 18 female students. The most important result showed that the impact of practical lectures program was more on female students than male student ones. The courage level male students was higher than that of female ones at the beginning of the year, but  it  was  similar at the end of the year.